Shaiva Dvarapala and female figures on the doorframe of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The doorframe of the garbhagriha (sanctum sanctorum) is adorned with two female figures, while the central positions on either side are occupied by Shaiva dvarapalas (door guardians). Completing the ensemble is the figure of Kubera, the God of wealth.